2022
DOI: 10.34123/semnasoffstat.v2022i1.1299
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Analysis Using K-Means Method to Classify Sumatera Regency and City Based on Human Development Index Indicator

Abstract: Human development progress in Indonesia is characterized by the increasing score of Human Development Index (HDI). HDI is an important indicator in measuring efforts to build the quality and equity of human life. HDI consists of four variables including life expectancy at birth, school continuity, average of school continuity and expenditure per capita. In this study, we classify districts or cities on the island of Sumatra based on HDI into three categories; high, middle, and low area. We use cluster analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…The algorithm of this method groups objects based on the distance between the objects and the centroid cluster [17] where the distance is obtained by an iterative process. The analysis needs to determine the number of k as input to the algorithm [12], [18]. The goal of K-Means clustering is to get clusters of objects by maximizing the similarity of objects within clusters (or minimizing variance within clusters) and maximizing the differences between clusters.…”
Section: A1 K-means Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The algorithm of this method groups objects based on the distance between the objects and the centroid cluster [17] where the distance is obtained by an iterative process. The analysis needs to determine the number of k as input to the algorithm [12], [18]. The goal of K-Means clustering is to get clusters of objects by maximizing the similarity of objects within clusters (or minimizing variance within clusters) and maximizing the differences between clusters.…”
Section: A1 K-means Methodsmentioning
confidence: 99%
“…The researchers found that the number of clusters is four clusters using K-Means [4], [5], [10] and Fuzzy C-Means [10], but two clusters for hierarchical clustering and five clusters for indah.fahmiyah@ftmm.unair.ac.id K-Medoids [5]. HDI grouping in a particular area in Indonesia was also carried out [1], [11], [12]. Grouping human development of countries in the world is also carried out using the K-means and Partitioning Around Medoids algorithms and offers cut-off values to classify countries with low (lower than 65), medium (65-85), and high (greater than 85) human development [13].…”
Section: Corresponding Authormentioning
confidence: 99%
See 1 more Smart Citation